Research on mechanics properties of crop stalks: A review - Dongdong, Du; jun, Wang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: As one of the foundational research areas in agricultural engineering, the study of agricultural materials includes an important branch: mechanics properties of crop stalks. This branch is now widely associated with design and improvement of agricultural equipment, breeding of new species, and development of reinforced composites. This article presents an overview of research on mechanics properties of crop stalks, including the mechanics measurement experiments, mechanics model and theory, microstructure and composition, and mechanics simulation experiments. The current research relies mainly on the mechanics theory of engineering material, neglects the fact that crop stalk is a biological material with complex structure, anisotropy, viscoelasticity and rheology. In addition, some simulation experiments are conducted in idealized conditions, beyond the application. Hence, the paper proposes to create new material models for crop stalks, conduct more practical and effective simulation experiments, and promote cooperation in interdisciplinary studies for the development of mechanics properties of crop stalks in the future research. Keywords: crop stalk, mechanics property, measurement, model, theory, microstructure, composition, mechanics simulation DOI: 10.3965/j.ijabe.20160906.1499 Citation: Du D D, Wang J. Research on mechanics properties of crop stalks: A review. Int J Agric & Biol Eng, 2016; 9(6): 10-19.